Testing Strategies of the In Vitro Micronucleus Assay for the Genotoxicity Assessment of Nanomaterials in BEAS-2B Cells - Cervena, Tereza; Rossnerova, Andrea; Zavodna, Tana; Sikorova, Jitka; Vrbova, Kristyna; Milcova, Alena; Topinka, Jan; Rossner, Pavel (Nanomaterials (Basel, Switzerland), 2021)
The evaluation of the frequency of micronuclei (MN) is a broadly utilised approach in in vitro toxicity testing. Nevertheless, the specific properties of nanomaterials (NMs) give rise to concerns regarding the optimal methodological variants of the MN assay. In bronchial epithelial cells (BEAS-2B), we tested the genotoxicity of five types of NMs (TiO2: NM101, NM103; SiO2: NM200; Ag: NM300K, NM302) using four variants of MN protocols, differing in the time of exposure and the application of cytochalasin-B combined with the simultaneous and delayed co-treatment with NMs. Using transmission electron microscopy, we evaluated the impact of cytochalasin-B on the transport of NMs into the cells. To assess the behaviour of NMs in a culture media for individual testing conditions, we used dynamic light scattering measurement. The presence of NMs in the cells, their intracellular aggregation and dispersion properties were comparable when tests with or without cytochalasin-B were performed. The genotoxic potential of various TiO2 and Ag particles differed (NM101 < NM103 and NM302 < NM300K, respectively). The application of cytochalasin-B tended to increase the percentage of aberrant cells. In conclusion, the comparison of the testing strategies revealed that the level of DNA damage induced by NMs is affected by the selected methodological approach. This fact should be considered in the interpretation of the results of genotoxicity tests.
Keywords: genotoxicity; cell line; micronucleus assay; DLS; nanomaterials